2022
DOI: 10.1088/1361-6587/ac65b0
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion density in the ion source SPIDER in Cs free conditions

Abstract: The SPIDER experiment, operated at the Neutral Beam Test Facility of Consorzio RFX, Padua, hosts the prototype of the H-/D- ion source for the ITER neutral beam injectors. The maximization of the ion current extracted from the source and the minimization of the amount of co-extracted electrons are among the most relevant targets to accomplish. The Cavity Ring-Down Spectroscopy diagnostic measures the negative ion density in the source close to the plasma grid (the plasma-facing grid of the ion acceleration sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…At present, the beam source is operated in pulsed mode and it is equipped with a number of beam diagnostics and source diagnostics (see [21] and references therein). The diagnostic calorimeter STRIKE [22], beam emission spectroscopy (BES) [23], optical cameras, Allison emittance scanner [24], single-beamlet current monitors (new diagnostics based on LEM sensors) provide independent measurements of the beam properties, while Langmuir probes [25], optical emission spectroscopy [26], cavity ring down spectroscopy [27], laser absorption spectroscopy [28], Langmuir-Tayor detectors [29] can provide insight on the plasma and surface processes inside the plasma source.…”
Section: Experimental Configuration Of Spider and Operation With Caesiummentioning
confidence: 99%
“…At present, the beam source is operated in pulsed mode and it is equipped with a number of beam diagnostics and source diagnostics (see [21] and references therein). The diagnostic calorimeter STRIKE [22], beam emission spectroscopy (BES) [23], optical cameras, Allison emittance scanner [24], single-beamlet current monitors (new diagnostics based on LEM sensors) provide independent measurements of the beam properties, while Langmuir probes [25], optical emission spectroscopy [26], cavity ring down spectroscopy [27], laser absorption spectroscopy [28], Langmuir-Tayor detectors [29] can provide insight on the plasma and surface processes inside the plasma source.…”
Section: Experimental Configuration Of Spider and Operation With Caesiummentioning
confidence: 99%
“…Some auxiliary experimental results on the axial plasma density distribution under various PG currents in the HUST source also demonstrated this phenomenon [29]. If the field strength continues to increase to a larger value (our setup cannot be reached yet due to the power source limitation), instead, it can penetrate deeper into the driver, depressing the production of ions, neutrals, and excited molecules, which will result in a decrease in electron density of the plasma in the extraction region [30,31]. The positive ion density, shown in figure 8(b), demonstrated a similarity to the electron density in both value and trend, indicating that the plasma at this position remained quasi-neutral.…”
Section: Pg Current Magnetic Filtermentioning
confidence: 65%
“…Indeed, a vertical nonhomogeneity of the beam current was identified; particularly, it was also found that the beam is peaked in each beamlet group [11]. The ratio between the co-extracted electron and the negative ion currents was found to be at least in the range of several tens [13].…”
Section: Introductionmentioning
confidence: 85%